Correlation between the Performance of Agricultural Extension Workers and the Behavior of Vegetable Farmers in Terjun, Medan Marelan, North Sumatra, Indonesia - Manik, Juita Rahmadani; Siregar, Gustina; Monika Ambarwati, (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
This study aims at assessing the performance of agricultural extension services (also known as agricultural advisory services) and the behavior of vegetable farmers while examining the correlation between these two variables. Data were collected through direct interviews, discussions with farmers, and on-site observations conducted in the Terjun region of Medan Marelan, North Sumatra, Indonesia. A simple random sampling method was employed, with 48 samples selected without consideration of population strata. This research adopts a descriptive and quantitative qualitative research approach. The findings reveal two key performance indicators for agricultural extension workers. First, the assessment of visits and training indicated an average score of 146.2, with a 76.14% rating, categorizing it as 'good.' Second, the evaluation of the extension workers' performance yielded a similar score of 146.2, also categorized as 'good.' The correlation analysis between farmer behavior and the performance of agricultural extension workers yielded three distinct outcomes. Firstly, the correlation between farmers' knowledge and the performance of extension workers resulted in a value of 0.175, indicating a very weak correlation with a significance value exceeding 0.05. Secondly, the correlation between farmers' characteristics and the performance of extension workers showed a coefficient of 0.014, suggesting a very weak correlation with a significance value exceeding 0.05. Lastly, the correlation between farmers' skills and the performance of extension workers resulted in a coefficient of 0.166, denoting a very weak correlation with a significance value exceeding 0.05.